Resolving confusions about jarrah dieback - don’t forget the plants - Davison, Elaine (Springer, 2014)
The name jarrah dieback has been used for two different disorders, leading to considerable confusion. It was coined in the 1940s to describe the sudden death of groups of jarrah (Eucalyptus marginata) trees in south western Western Australia, which occurred on poorly drained sites, following exceptionally heavy rainfall. In the 1960s these sites were shown to be infested by Phytophthora cinnamomi and jarrah deaths were attributed to it, even though it was only isolated from 5 % of sampled trees. Also the definition of jarrah dieback was expanded to include deaths of many other plants on infested sites, from which P. cinnamomi was more readily isolated. Jarrah trees die from severe water deficiency, indicating problems with water conduction through roots. Xylem vessel diameters vary along roots, being narrow at the root collar, while distally they are larger, providing water storage. Jarrah transpires vigorously during summer, accessing water at depth on sites with deep soil, but being more dependent on internally stored water when root systems are shallower. Following waterlogging, sapwood vessels become blocked with tyloses, reducing both conductivity and potential water storage; such trees may have insufficient water reserves for summer survival. In jarrah P. cinnamomi is unlikely to cause water deficiency because sapwood invasion is rapidly contained in healthy roots. Recent investigations into P. cinnamomi invasion and host responses in other plants show that it can potentially cause a vascular wilt in Banksia spp. and chronic, symptomless infections in herbaceous plants. Susceptibility to waterlogging damage, and/or mortality resulting from infection by P. cinnamomi can only be clarified by detailed knowledge of the hosts and their vulnerabilities. This is essential for making diagnoses, devising management strategies, and avoiding the confusions of the past.